Multi-level robot management - Ling, Ngee Hung (Nanyang Technological University, 2020)
In collaboration with Avetics Singapore, the project aims to build a cloud platform which is capable of integrating, remote-controlling and orchestrating of multiple robots concurrently to complete a variety of large-scale and complex missions, while using ground stations to overcome latency and deployment issues. This particular project aims to conduct a round trip delivery, using robots, between different points of a logistics hub so as to eliminate the need for human intervention in those high risk areas and reduce cost in that particular leg of logistics process chain. Coordination of this mission will require multiple data observations and assessment, including route planning and mapping, computer vision, obstacle avoidance, video streaming and robot telemetry communications. The project employs a multitude of technologies and open source projects. The core architecture is based off distributed computing. There will 3 main components to the software. A client facing frontend, a server for relaying of messages and assessing of databases and lastly an onboard program which serves as the operating program of the robots. The robots utilized in this project are highly confidential but they need to have high reliability and developer’s kit to allow quick integration of software. The specific technologies used for each component will be further discussed in the report. The software system will also be deployed in the cloud servers so as to increase accessibility and leverage on existing web technologies. After the deployment of the projects, a series of testing will be conducted so as to ensure the reliability of the software system. The end project achieved real time management of multiple robots through a web application interface. Mission progress, information on the surroundings and the robots involved were also visualized on the ground information system of the web application. The application serves as a tool to help the coordination and management of multiple robots. This increases the possibilities of automated robot operations in the world. With more complex coordination being made possible and the increase digitalization of devices, task with higher complexity can be executed. At the same time, better observations and data could be collected. With an increasing adoption of internet things, increase in connectivity and the race to raise productivity, such an application will become more of a necessity over time. The report documents the development process and progress of the project. Analysis on different components of the software system was conducted, based on criteria such as performance, time required for development and level of integration possible with third party libraries. An evaluation then covers the overall performance of the final product in the form of a numerical analysis on the performance and its capabilities. The finalized architecture is a key result which can potentially serve as a template for future relevant works.